Bromelain regulates TRP channels to induce orofacial nociception relief in adult zebrafish - Saulo Rodrigo Lucas Ribeiro; Sacha Aubrey Alves Rodrigues Santos; Ana Lívia Oliveira de Sousa Rodrigues; Gabriella Mesquita de Sena; Antônio Eufrásio Vieira-Neto; Adriana Rolim Campos (Biochemistry and Biophysics Reports, 2024)
Bromelain, the main protease enzyme found in the pineapple plant (Ananas comosus), has had its antinociceptive effect previously demonstrated. This investigation aimed to appraise the role of TRP (Transient Receptor Potential) channels in the nociception-relieving effects of bromelain in the orofacial region of adult zebrafish. The animals were pretreated with bromelain (3.0, 10.0 or 30.0 mg/mL; gavage) and submitted to open field and acute orofacial (capsaicin - TRPV1 agonist, cinnamaldehyde - TRPA1 agonist or menthol - TRPM8 agonist) nociception tests. The investigation also explored the contribution of central afferent C-fibers. Naive groups were included for comparison. Bromelain did not independently affect the zebrafish movement patterns. However, bromelain decreased the nociceptive responses elicited by all three TRP channel activators. Capsazepine (TRPV1 inhibitor) and AMTB (TRPM8 inhibitor), but not HC-030031 (TRPA1 inhibitor), prevented the antinociceptive effect of bromelain. Moreover, capsaicin-induced desensitization effectively nullified the antinociceptive effect of bromelain. Collectively, these findings corroborate the therapeutic relevance of bromelain as a suppressor of orofacial nociception, which seems to be intricately connected to the modulation of TRP channels.